Will the widespread use of cashless payments reduce the frequency of the use of cash payments? - Hiroshi Fujiki (Review of Economic Analysis (REA), 2022)
Will the widespread use of cashless payments reduce the frequency of the use of cash payments? This question is important because the major costs of cash use are fixed costs that would only be reduced if the frequency of cash payments substantially decreased, and thus the extent of the reduction of the cost of cash use depends on the frequency of cash use after the widespread use of cashless payment methods. Using the data from the Financial Literacy Survey 2019 in Japan, this paper shows that the frequency of cash use for those who use both cash and noncash payment methods and that of those who exclusively use cash are about once in 2.3 days and about once in 2 days, respectively, and thus there is only a slight difference. The result did not change even if a regression model for cash usage was used that considers the endogenous choice of payment methods or if counterfactual simulations of the decrease in consumers' willingness to use cash were conducted. The results suggest that the benefit of reducing the cost of cash use due to the widespread use of cashless payment methods is overestimated because the frequency of the use of cash payments is unlikely to decrease despite the use of cashless payment methods.
Keywords: D12; D14; E41; G51; G53; 330; Cash demand; costs of cash usage; payment methods